Farmers’ Personal Hygiene to Prevent Exposure to Soil Transmitted Helminth (STH) Infection Agents - Kurniyawan, Enggal Hadi; Dewi, Ratna Kusuma; Mayasari, Yunita; Aisyah, Ica Nur; Nabela, Mareta; Afandi, Alfid Tri; Nur, Kholid Rosyidi Muhammad (Journal of Local Therapy, 2025)
STH (Soil-Transmitted Helminth) infection remains a complex problem in endemic areas today, especially in developing countries with significant challenges to the population’s lack of environmental sanitation and personal hygiene. This study aims to prevent work accidents and provide knowledge about occupational health and safety to farmers using complete PPE to avoid exposure to STH worm infections. Literature or reference searches conducted during the literature review use three web journal databases: Google Scholar, PubMed, and Science Direct. Some words are searched using the keywords "Farmer" AND "Soil-Transmitted Helminth " AND "Infection" OR "Infectious" AND "Personal Hygiene ." The articles use ten journal articles spanning the last five years. Worm infection caused by Soil-Transmitted Helminth is a public health problem in Indonesia. The risk of worm infection or STH can be prevented through improved personal hygiene and education to change the pattern of behavior of farmers who are not good, especially when in direct contact with the soil.